2004
DOI: 10.1080/0891693042000196200
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells and Innate Cytokines are Associated with Susceptibility to Autoimmune Heart Disease Following Coxsackievirus B3 Infection

Abstract: The development of autoimmune disease involves a combination of genetic and environmental factors. Many autoimmune diseases are believed to be triggered by viral infections. Since the early, natural immune response to infection can determine the later development of the adaptive immune response, innate immunity likely influences the progression from viral immunity to autoimmunity. To investigate the role of the innate immune response on susceptibility to autoimmune disease, we compared the early cytokine respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 63 publications
6
98
0
Order By: Relevance
“…2E). MC are known to release an array of preformed and secreted mediators after activation, including cytokines, that may directly influence the function of the adaptive immune response (15)(16)(17). Our results provide evidence that MC may be important immunoregulatory cells during the initiation of immune responses.…”
Section: Resultssupporting
confidence: 55%
“…2E). MC are known to release an array of preformed and secreted mediators after activation, including cytokines, that may directly influence the function of the adaptive immune response (15)(16)(17). Our results provide evidence that MC may be important immunoregulatory cells during the initiation of immune responses.…”
Section: Resultssupporting
confidence: 55%
“…We also found that increased TNF-␣ levels in the heart during the innate response to viral infection are associated with the development of chronic myocarditis (4,(35)(36)(37). In contrast, TNF-␣ has been found to play a critical role in the control of certain viral infections such as murine cytomegalovirus (38, 39), but not for other viruses such as LCMV (40).…”
Section: Tnfrp55 Deficiency Does Not Increase Viral Replication or Mymentioning
confidence: 64%
“…that is associated with the development of DCM (3). Susceptible BALB/c mice respond to CVB3 infection with elevated levels of TNF-␣, IL-1␤, and IL-12p70 in the heart during the innate response (4). We have shown that increased IL-1␤ and IL-18 levels in the heart correlate with increased acute CVB3 myocarditis, and are mediated by TLR4 and IL-12R␤1 signaling (5).…”
Section: Il-12 Protects Against Coxsackievirus B3-induced Myocarditismentioning
confidence: 85%
See 1 more Smart Citation
“…Other cells or cellular products including NK cells (2), mast cells (31), and complement (2) also influence disease susceptibility. Interestingly, a subset of TCR␣␤ ϩ CD4 Ϫ CD8 Ϫ double negative cells were found in lesions of autoimmune myocarditis (30), arthritis (32), and encephalomyelitis (33) developed in CD4-deficient mice, suggesting these cells may be capable of obviating the requirement for CD4 ϩ T cells and subserve the effector function.…”
Section: Discussionmentioning
confidence: 99%